The Muslim woman and self: Reframing conflict and spiritual awakening in Asra Nomani’s standing alone - Roselind, R; Ruzy Suliza Hashim; Raihanah, M.M (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
This paper focuses primarily on Asra Nomani’s self-narrative, Standing Alone and the intertwined concepts of self, conflict and spiritual awakening. Previous extensive works done in women’s scholarship and Islam were mainly influenced by Western ideological constructs which predominantly view women and Muslims as possessing monolithic qualities. As such, this paper critically explores Standing Alone as it offers an alternative view to the stereotypical depiction of Muslim women. This study adopts an eclectic framework based on Slee’s (2004) stages/generative themes of concern and the Islamic Paradigm of the Correlational Self. The analysis traces and explores thematic concerns particularly Nomani’s physical and spiritual journeys which transcend both geographical and imaginary borders and spaces. These transformations are reflected in her stages of conflict and spiritual awakening. They are also revealed through the depiction of Nomani’s relationships with God and Others, termed as “hablum min Allah wa hablum min al-nas” and her spiritual battles against wrongdoings, labeled as “amr bi al-ma’aruf wa al-nahyi ‘an al-munkar” which are two Islamic concepts informed by the Islamic Paradigm of the Correlational Self. Thus, through careful examination of Standing Alone based on this framework, we challenge much-accepted assumptions of a monolithic Islam as typically static and traditional. This self-narrative, which showcases an example of the multiplicity and fluidity of the Muslim self, proves that present available frameworks are insufficient in capturing the rich, subtle nuances of symbolic Muslim women’s traditions.